2016
DOI: 10.1186/s40880-016-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

The expression and prognostic value of protein tyrosine kinase 6 in early-stage cervical squamous cell cancer

Abstract: BackgroundProtein tyrosine kinase 6 (PTK6) is overexpressed in many epithelial tumors and predicts poor prognosis. However, PTK6 expression status and its role in cervical squamous cell cancer are unknown. This study aimed to investigate the expression level and clinical significance of PTK6 in early-stage cervical squamous cell cancer.MethodsQuantitative reverse transcription-polymerase chain reaction (qRT-PCR) and western blotting analysis were performed to detect PTK6 mRNA and protein expression levels in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Patient tissue analysis of bladder 62 , cervical 4 , prostate 63 , and non-small cell lung cancer 64 showed that higher expression of BRK is associated with poorer overall survival. Particularly, in cervical 4 , thyroid 65 , and bladder cancer 62 , BRK expression levels are also associated with tumor grade and severity. Interestingly in breast cancer, Aubele et al highlighted in year 2007 and 2008 that BRK appears to be a positive indicator of disease-free survival 66 , 67 .…”
Section: Therapeutic Significancementioning
confidence: 99%
“…Patient tissue analysis of bladder 62 , cervical 4 , prostate 63 , and non-small cell lung cancer 64 showed that higher expression of BRK is associated with poorer overall survival. Particularly, in cervical 4 , thyroid 65 , and bladder cancer 62 , BRK expression levels are also associated with tumor grade and severity. Interestingly in breast cancer, Aubele et al highlighted in year 2007 and 2008 that BRK appears to be a positive indicator of disease-free survival 66 , 67 .…”
Section: Therapeutic Significancementioning
confidence: 99%
“…The PCR primers sequences of ASF1B are as follows: forward 5′-TGGACAGGAGTTCATCCGAGTG-3′ and reverse 5′-GTCCCAGTTGATATGGAAGCGG-3′. The 2−ÄÄCt (cycle threshold) method were used, where the expression of GADPH was regarded as an endogenous standard to normalize the relative changes in ASF1B expression [5]. Primers for GADPH are as follows: forward 5'-AGAAGGCTGGGGCTCATTTGC-3' and reverse 5'-ACAGTCTTCTGGGTGGCAGTG-3'.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Moreover, a variety of novel oncogenes have been identi ed as signi cant biomarkers that are associated with unsatisfactory clinical outcome of cervical neoplasm [5][6][7]. However, they are not su ciently powerful to predict clinical outcome, and their clinical applications are limited because of poor sensitivity and speci city.…”
Section: Introductionmentioning
confidence: 99%
“…PTK6 expression was first identified in metastatic breast cancer [6][7][8][9] and subsequently detected in several other cancers of the ovary [10], head and neck [11,12], lung [13,14], esophagus [15], cervix [16], bladder [17], pancreas [18] and stomach [19].…”
Section: Introductionmentioning
confidence: 99%